Financing a Water Secure Future. - OECD. (Organization for Economic Cooperation & Development, 2022)
This report presents a summary of the key challenges and opportunities related to financing that contributes to water security and sustainable growth distilling insights from the Roundtable on Financing Water and related analyses. It covers a broad range of water-related investments, including water and sanitation services, water resources management, agricultural water and managing water-related risks ("too much", "too little" and "too polluted").